2012
DOI: 10.1097/acm.0b013e31826768d4
|View full text |Cite
|
Sign up to set email alerts
|

“The Benefits Make Up for Whatever Is Lost”

Abstract: Residents were flexible and altruistic, accepting trade-offs in their own experiences in favor of patient care. Education was negatively affected. This study highlights the importance of carefully studying changes to look for anticipated and unanticipated consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…3,24 While some researchers found that residents reported an improvement in their overall well-being due to the implementation of work hour limitations, they also reported that such work hour limitations negatively impacted patient care and resident education. 28,29 One of the suggested solutions to overcome these issues is transitioning to the night float system. Although different models exist, the night float system was implemented in different institutions in Canada with the aim of restricting resident duty hours and complying with the duty hour restrictions policy.…”
Section: Results a Total Of 314 Pediatric Residents Representing 111%mentioning
confidence: 99%
“…3,24 While some researchers found that residents reported an improvement in their overall well-being due to the implementation of work hour limitations, they also reported that such work hour limitations negatively impacted patient care and resident education. 28,29 One of the suggested solutions to overcome these issues is transitioning to the night float system. Although different models exist, the night float system was implemented in different institutions in Canada with the aim of restricting resident duty hours and complying with the duty hour restrictions policy.…”
Section: Results a Total Of 314 Pediatric Residents Representing 111%mentioning
confidence: 99%
“…[22][23][24][25] However, at the same time, residents also noted perceived benefits, such as strengthened relationships with colleagues and developing professional autonomy. 26 These tensions were not easily reconciled.…”
Section: Discussionmentioning
confidence: 99%